2004
DOI: 10.1074/jbc.m311773200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pathway Involving Progesterone Receptor, 12/15-Lipoxygenase-derived Eicosanoids, and Peroxisome Proliferator-activated Receptor γ Regulates Implantation in Mice

Abstract: The 12/15-lipoxygenases (12/15-LOX) catalyze the stereo-specific oxygenation of arachidonic and linoleic acids into a complex series of signaling molecules, including the hydroxyeicosatetraenoic acids (HETEs) and hydroxyoctadecadienoic acids (HODEs). Our previous studies, using high density oligonucleotide microarrays, suggested a novel link between progesterone receptor (PR) signaling and 12/15-LOX-mediated fatty acid metabolism in preimplantation mouse uterus. In this paper, using PR knockout mice, we establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 51 publications
3
63
0
1
Order By: Relevance
“…Several studies have shown that the LOX15-derived lipid metabolites 9-HODE and 13-HODE activate PPARg and its downstream gene networks. 13,29 We could not detect directly these LA metabolites; however, reduction of LAinduced growth inhibition by PPARg antisense S-ODN treatment supports our hypothesis that LA is metabolized to PPARg ligands in COX-2-negative colon epithelial cells.…”
Section: Discussionmentioning
confidence: 63%
“…Several studies have shown that the LOX15-derived lipid metabolites 9-HODE and 13-HODE activate PPARg and its downstream gene networks. 13,29 We could not detect directly these LA metabolites; however, reduction of LAinduced growth inhibition by PPARg antisense S-ODN treatment supports our hypothesis that LA is metabolized to PPARg ligands in COX-2-negative colon epithelial cells.…”
Section: Discussionmentioning
confidence: 63%
“…Immunohistochemistry-Polyclonal antibody against FRA-1 was used for immunohistochemistry as described previously (20). Briefly, paraffin-embedded uterine tissue was sectioned at 4 m and mounted on slides.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry and Immunocytochemistry-Paraffin-embedded endometrial sections were subjected to immunohistochemistry as described previously (36). Polyclonal antibodies against BMP2 and type II BMP receptor were obtained from Santa Cruz Biotechnology, Santa Cruz, CA.…”
Section: Materials-recombinant Human Bmp2 Was Purchased From Randd Systmentioning
confidence: 99%